(untitled) (Journal of the College of Basic Education, 2022)
The Abbasid poet continued to carry the product of spinning poetry, in which the beauty of women and nature blended, as the poets of this period were fascinated by them, so the poets chose the scenes of the flowering and living nature to resemble the beauty of women.My research dealt with the tributaries of the image of the woman in the poetry of Khaled Al-Kateb (269 AH), the living and silent nature as a model, so I shed light on it, because it constitutes an important source of the poet’s sources. The silent nature was more responsive to the poet than the living nature, with its perceptions expressing his self-inspiration and participating in building the poet’s image of women. It occupied a large part of the poet’s memory and provided him with many meanings and images.